Soybean green manure intercropping improves citrus quality by improving soil quality and altering microbial communities - Deng, Sufeng; Huang, Binbin; Zeng, Bin; Cao, Sheng; Gong, Biya; Liao, Wei; Zhang, Wen; Luo, Sainan; Yang, Shuizhi (Frontiers in Plant Science, 2025)
IntroductionIntercropping leguminous green manure in orchards represents a widely adopted agroecological practice that concurrently influences soil physicochemical properties, microbial communities, and crop performance. However, the temporal mechanisms by which different durations of soybean green manure (SGM) intercropping regulate soil-plant-microbe interactions remain insufficiently understood. This study elucidates the impact of SGM intercropping duration on ecosystem functionality in citrus orchards.MethodsA multi-year field experiment compared SGM intercropping durations (0-, 1-, and 2-year treatments). We assessed citrus fruit quality parameters (total soluble solids, TSS; sugar-acid ratio, TSS/TA) and soil properties (pH, available nitrogen, total nitrogen, available phosphorus, available potassium, and organic matter). Microbial community structure was analyzed via high-throughput sequencing. Spearman correlation analysis (|ρ| ≥ 0.8, p < 0.05) delineated networks among intercropping duration, soil parameters, keystone microbial taxa (e.g., Proteobacteria, Acidobacteriota, Ascomycota), and fruit quality indicators.ResultsThe two-year intercropping treatment (T2) significantly enhanced fruit quality: TSS increased by 11.66% and the sugar-acid ratio (TSS/TA) by 41.95% (p < 0.05). Soil properties improved markedly: pH rose by 0.42 units, while AN, TN, AP, AK, and OM increased by 41.80%, 9.15%, 16.78%, 100.50%, and 79.53%, respectively (p < 0.05). Microbial communities underwent structural reorganization, exhibiting increased α-diversity, enhanced network complexity, and selective enrichment of beneficial taxa including Actinobacteria, Mortierellales, and Ascomycota. Correlation networks revealed significant associations among intercropping duration, soil parameters, keystone microbes, and fruit quality.DiscussionThis study demonstrates that SGM intercropping enhances fruit quality through dual mechanisms: (1) amelioration of soil properties (pH elevation and improved nutrient availability), and (2) functional restructuring of microbial communities. Notably, specific taxa such as Actinobacteria play pivotal roles in nutrient cycling. Our findings provide empirical evidence for microbiome-mediated optimization of soil functionality, offering a sustainable rehabilitation strategy for degraded orchards and reinforcing the scientific value of ecological intensification in perennial cropping systems.